Networking wireless sensors - Krishnamachari, Bhaskar (Cambridge University Press, 2005)
This book provides a comprehensive and organized survey of the field of wireless sensor networks, one of the most rapidly developing new information technologies, with a wide range of applications. Ideal for researchers and practioners, it also contains many exercises and can be used in a graduate course on Networks.